Duloxetine prevents the effects of prenatal stress on depressive-like and anxiety-like behavior and hippocampal expression of pro-inflammatory cytokines in adult male offspring rats. Issue 55 (December 2016) - Zhang, Xiaosong; Wang, Qi; Wang, Yan; Hu, Jingmin; Jiang, Han; Cheng, Wenwen; Ma, Yuchao; Liu, Mengxi; Sun, Anji; Zhang, Xinxin; Li, Xiaobai
Highlights: Prenatal stress (PNS) induced an increase in hippocampal IL-6 mRNA expression level. PNS increased anxiety- and depression-like behaviors in adult male offspring. Duloxetine decreased anxiety- and depression-like behavior in PNS offspring. Duloxetine normalizes the increased hippocampal IL-6 mRNA level induced by PNS. Abstract: Stress during pregnancy may cause neurodevelopmental and psychiatric disorders. However, the mechanisms are largely unknown. Currently, pro-inflammatory cytokines have been identified as a risk factor for depression and anxiety disorder. Unfortunately, there is very little research on the long-term effects of prenatal stress on the neuroinflammatory system of offspring. Moreover, the relationship between antidepressant treatment and cytokines in the central nervous system, especially in the hippocampus, an important emotion modulation center, is unclear. Therefore, the aim of this study was to determine the effects of prenatal chronic mild stress during development on affective-like behaviors and hippocampal cytokines in adult offspring, and to verify whether antidepressant (duloxetine) administration from early adulthood could prevent the harmful consequences. To do so, prenatally stressed and non-stressed Sprague-Dawley rats were treated with either duloxetine (10 mg/kg/day) or vehicle from postnatal day 60 for 21 days. Adult offspring were divided into four groups: 1) prenatal stress + duloxetine treatment, 2) prenatal stress + vehicle, 3) duloxetine treatment alone, and 4) vehicle alone. Adult offspring were assessed for anxiety-like behavior using the open field test and depression-like behavior using the forced swim test. Brains were analyzed for pro-inflammatory cytokine markers in the hippocampus via real-time PCR. Results demonstrate that prenatal stress-induced anxiety- and depression-like behaviors are associated with an increase in hippocampal inflammatory mediators, and duloxetine administration prevents the increased hippocampal pro-inflammatory cytokine interleukin-6 and anxiety- and depression-like behavior in prenatally stressed adult offspring. This research provides important evidence on the long-term effect of PNS exposure during development in a model of maternal adversity to study the pathogenesis of depression and its therapeutic interventions.